Healthcare cost of HER2-positive and negative breast tumors in the United States (2012–2035). (November 2017) - Tartari, Francesca; Santoni, Matteo; Pistelli, Mirco; Berardi, Rossana
Highlights: The approach to advanced breast cancer has been revolutionized by targeted agents. The total cost of HER2-positive patients was estimated for $2, 719, 542, 347 in 2012. The total estimated cost for HER2-negative patients in 2012 was $8, 376, 028, 459. In 2035, we estimated a cost of $3.6 and $11.2 bilions for HER2+ and HER2− tumors. The cost of HER2-negative tumors should be carefully evaluated in the coming years. Abstract: Background: In this study, we estimated the current and future costs related to the use of targeted agents in patients with HER2-positive and negative advanced breast cancer (BC), aimed at identifying the subgroup associated with the higher cost in the coming years. Methods: We calculated the patient cost considering an ideal patient who received therapeutic sequences including all approved agents for HER2-positive or negative BC. The duration of treatment was estimated by the median Progression-Free Survival (PFS) reported in the phase III trials which have led to the approval of these drugs by the US Food and Drug Administration. The estimated number of BC patients in the US from 2012 to 2035 refers to data published by the World Health Organization. Results: The per patient cost was $292, 155 for HER2-positive and $224, 955 for negative tumors, respectively. The total cost for HER2-positive patients was estimated for 2012 at $2, 719, 542, 347, with an annual increase ranged from 4.3 (for 2035) to 7.7% (for 2020), leading to a total expense of $3, 648, 232, 975 in 2035. Otherwise, the total cost for HER2-negative patients in 2012 was estimated as $8, 376, 028, 459, with an increase of more than $2.5 billion from 2012 to 2035. The estimated cost for HER2-negative patients was $5.6 billion higher that for HER2-positive tumors, raising to $7.6 billion to 2035. Conclusions: Our data strongly suggest that cost-analyses should be carefully evaluated in the coming years, in particular in patients with HER2-negative tumors.